Thrombolytic Potentials of Some Medicinal Plants Used by the Local People for Cardiovascular Diseases in Bangladesh - Uddin, Mohammad Zashim; Rifat, Atiya Begum; Mitu, Farhana Yesmin; Haque , Tahmina; Mazid, Md Abdul (Bangladesh Journal of Plant Taxonomy, 2021)
Cardiovascular diseases (CVDs) are one of the major causes of death in the world. Medicinal plants with thrombolytic properties may be used as an alternative to modern medicines for CVDs. The present study was aimed to evaluate the thrombolytic potential of six medicinal plants available in Bangladesh using an in vitro clot lysis method where streptokinase and ethanol were used as a positive and negative control, respectively. Ethanolic extract at a dose of 10 mg/ml of Arjun tree (Terminalia arjuna), Garlic (Allium sativum), Elephant apple (Dillenia indica), Amla (Phyllanthus emblica), Yellow mombin (Spondias pinnata) and Burmese grape (Baccaurea ramiflora) showed 14.18 ± 1.23%, 10.72 ± 0.78%, 8.25 ± 0.42%, 7.08 ± 0.64%, 5.42 ± 0.47% and 2.47 ± 0.19% clot lysis, respectively, whereas the standard drug streptokinase lysed 41.11±0.31% clot at a dose of 30,000 IU. From the data, it is evident that ethanolic extracts of six selected medicinal plants possess a moderate to insignificant thrombolytic activities. Among these plants, Arjun tree and Garlic exhibited the highest thrombolytic activity and the Burmese grape showed the lowest thrombolytic activity. Through our study, it could be concluded that Arjun tree, Garlic, and Elephant apple might be used as traditional healing purposes of CVDs. However, further animal studies will prove the scientific justification of their uses. Conservation efforts should be given for Arjun tree, Elephant apple, Yellow mombin, Burmese grape, and Amla to save these plants from extinction in nature. Bangladesh J. Plant Taxon. 28(2): 405-412, 2021 (December)